Modeling and analysis of cascading node-link failures in multi-sink wireless sensor networks. (May 2020) - Fu, Xiuwen; Yang, Yongsheng
Highlights: We present a cascading node-link model for multi-sink WSNs. We propose two sink-oriented load metrics to measure the load distribution on sensor nodes and wireless links respectively. We evaluate the network robustness under link attacks and node attacks. We explore the impacts of critical thresholds on the cascading robustness of the network. Abstract: Due to the prominent advantages in network lifetime and energy balance, the application of multi-sink wireless sensor networks (WSNs) is becoming more and more widespread. However, their cascading robustness is still rarely studied. Therefore, in this paper, a realistic cascading model for multi-sink WSNs is proposed. In this model, two load metrics are proposed to characterize the load distributions of sensor nodes and wireless links, and the cascading process of the network is jointly promoted by node overload events and link overload events, which can better reflect the cascading characteristics of multi-sink WSNs in practical scenarios. In addition, we focus on the cascading robustness of the network in the face of node attacks and link attacks. Through extensive experiments, we found that there are critical thresholds for both node capacity and link capacity, which can determine whether capacity expansion is helpful; there is a critical threshold for network load distribution, which can determine whether cascading failures occur; node attacks are more likely to trigger cascading failures than link attacks; increasing node capacity can more effectively reduce the damage of cascading failures to the network. The discovery of the above results can provide theoretical guidance for users to build a more robust multi-sink WSN against cascading failures.